Concrete Construction Safety: Investigating (Western) Australian Formwork Practice - Whyte, Andrew; Brandis, Paul (RICS, 2011)
Preventing accidents from occurring is a primary concern for the Australian construction industry. One area where incidents have occurred, at a more than acceptable rate, is in the use of formwork; recent formwork failures in Australia illustrate these are just as significant as a permanent structure failure. Whilst most formwork failures are found to concern differing inadequacies in practice, the occurrence of formwork failures may be prevented by targeting reform at their root cause; this paper presents the findings of detailed investigations examining the guidance and legislation governing formwork practice in Australia. An analysis of documentation governing Australian formwork practice, alongside industry perceptions provide a rounded and extensive view of the current situation. Findings highlight the limitations of using a legislative-based model of control, and also express the importance of formwork design education and training.